Serum circulating miRNA‐342‐3p as a potential diagnostic biomarker in parathyroid carcinomas: A pilot study. Issue 4 (29th July 2021) - Krupinova, Julia; Mokrysheva, Natalya; Petrov, Vasiliy; Pigarova, Ekaterina; Eremkina, Anna; Dobreva, Ekaterina; Ajnetdinova, Alina; Melnichenko, Galina; Tiulpakov, Anatoly
Abstract: Objective: To compare the serum miRNA expression profiles between patients with benign and malignant parathyroid tumours. Background: Despite recent advances in molecular biology, a histological tissue biopsy is still the method of choice used to diagnose most cancers. The preoperative cytology is not an applicable method for diagnosis of parathyroid cancer (PC); therefore, huge interest exists in terms of finding alternative methodologies to seek specific cancer biomarkers. Design: A retrospective cross‐sectional study. Patients and Methods: Serum samples of patients with PC ( n  = 13) and parathyroid adenoma (PA) ( n  = 11), age ( p  = .999) and sex ( p  = .999) were matched and examined via the simultaneous comparative expression analysis of 754 microRNAs (miRNAs). The «TaqMan OpenArray Human MicroRNA Panel» (Applied Biosystems) was used to conduct real‐time PCRs using the «QuantStudio 12К Flex» station (Life Technologies). Results: According to the results of a pilot study, significant changes in expression levels between the PC group and the PA group (control) ( p  < .05) were observed for 17 miRNAs. Among them, the downregulation of miRNA‐342‐3p met the Benjamini‐Hochberg adjustment criteria for multiple comparisons ( p  = .02). Conclusions: Serum miRNA‐342‐3p could be a promising biomarker for PC to improve diagnosis and prognosis. Abstract : The main objective of this study was to compare the serum miRNA expression profiles between benign and malignant parathyroid tumors. To the best of our knowledge, this study is the first report on serum miRNA profiles derived from PC patients.